Dilemma-Based Decision-Making in EDIH Ecosystem’s : Insights Into Innovation Leadership - Ihamäki, Pirita; Kuoppakangas, Päivikki; Kaivo-oja, Jari (United States, 2026)
Decision-making in complex innovation ecosystems, such as European Digital Innovation Hubs (EDIHs), involves navigating strategic and ethical dilemmas. Despite EDIHs’ growing role in Europe’s digital transformation, limited research explores how leaders manage conflicting priorities. This study examines how dilemma-based decision-making shapes innovation leadership and dynamic capabilities in EDIHs. Grounded in Hampden-Turner’s dilemma theory and Teece’s dynamic capabilities framework, the study used a qualitative survey with 20 responses. The survey assessed leadership models, adaptability, and strategic decision-making. Findings reveal leaders frequently face tensions—such as balancing financial sustainability with ethical neutrality or short-term KPIs with long-term impact. Their ability to reconcile these dilemmas is vital for fostering innovation, trust, and resilience. This study contributes to dilemma-based decision-making, enhances innovation leadership, and activates dynamic capabilities within EDIHs. The results provide practical insights for policymakers, ecosystem designers, and innovation leaders aiming to strengthen the role of EDIHs in Europe’s digital future.
Human Factors in Design, Engineering, and Computing : Proceedings of the AHFE International Conference on Human Factors in Design, Engineering, and Computing (AHFE 2025 Hawaii Edition), Hawaii, USA 8-10, December 2025